The Potential Secondary Metabolites of Macroalgae Sargassum polycystum C. Agardh (1824) from the coast of West Aceh as Raw Material of Body Scrub - Mohamad Gazali; Nurjanah Nurjanah; Amir Husni; Chairun Nufus; Bintan Rahma Aulia; Citra Dina Febrina; Rina Syafitri (Universitas Gadjah Mada, 2022)
Sargassum polycystum is one brown seaweed with a rich alginate source. The previous study showed that S. polycystum could be used as a cosmeceutical raw material because of its natural attribute and safe. S. polycystum always grows in many coastal of Indonesia. This study aims to characterise brown seaweed (S. polycystum) as the raw material of the body scrub. The research method includes the extraction, phytochemical assay, antioxidant assay, and total phenolic content-the phytochemical screening-detected alkaloid and steroid compounds in S. polycystum extract. The antioxidant activity by using the CUPRAC method showed the ethanol extract was 53.55±1.07 µM/g and FRAP was 201.95±6.33 µM/g with total phenolic content was 177.647±21.39 Mg GAE/g. We compared the antioxidant capacity of the body scrub by adding brown seaweed of S. polycystum 7% (S7) used the CUPRAC method was 34.23±0.33 µM/g, and FRAP was 124.05±1.87 µM/g with total phenolic content was 416.31±78.44 Mg GAE/g. Kruskal Wallis's analysis showed that adding brown seaweed S. polycystum with different formulas influenced the panellist's preference for smearing ability, odor, texture, colour, and consistency parameters. According to the Mean rank obtained, the level of preferences of the panellists was gained from product S7 namely body scrub with the addition of brown seaweed S. polycystum as much as 7%. It is indicated that the brown seaweed S. polycystum possesses potentially body scrub raw material that is prospective in the cosmeceutical industry.